PENINGKATAN PARTISIPASI SISWA DALAM PEMBELAJARAN MATEMATIKA MELALUI MODEL PEMBELAJARAN KOOPERATIF TIPE TEAMS GAMES TOURNAMENT PADA SISWA KELAS X MA MAZROATUL ULUM PACIRAN - Haliza, Nur Rahma; Masamah, Ulfa (Galois: Jurnal Penelitian Pendidikan Matematika, 2025)
Lack of student involvement and low level of student participation in the mathematics learning process. During the learning process, students are less actively involved and often chat with their deskmates. To overcome this, researchers applied a cooperative learning model of the Teams Games Tournament (TGT) type. This study is a type of classroom action research with a cycle model that includes four stages: planning, action implementation, observation, and reflection. Data collection techniques include observation, interviews and documentation. The instruments in this study were observation sheets and interviews. The type of data analysis used in this study was qualitative analysis reinforced with descriptive quantitative data. The results of the analysis showed that in the pre-cycle stage, the average student participation was at 14.8%, the average student participation level in cycle I was 37.4%, and the average student participation level in cycle II was 87.0%. The three data indicate an increase in student participation, which is 22.6% from pre-cycle to cycle I, and 49.6% from cycle I to cycle II. The Teams Games Tournaments learning model applied in mathematics learning has a positive impact on increasing the learning participation of class X students of MA Mazroatul Ulum Paciran. This is shown by students expressing opinions and providing responses in the mathematics learning process.